2015
DOI: 10.1080/19440049.2015.1078915
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of tulathromycin in edible tissues of healthy and experimentally infected pigs withActinobacillus pleuropneumoniae

Abstract: The aim of this study was the comparison of the tissue pharmacokinetics of tulathromycin in healthy pigs and pigs experimentally infected with Actinobacillus pleuropneumoniae (App). Tulathromycin was given to 24 healthy and 24 infected pigs by intramuscular injection at a single dosage of 2.5 mg kg(-1) body weight (b.w.). Pigs were euthanised at each group and then samples of liver, kidney, muscle, injection site and skin with fat were taken at scheduled time points. Drug concentrations were determined by LC-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…However, disease studies using animal models have demonstrated a positive correlation efficacy with extravascular or tissue concentrations of the antibiotics mentioned above the minimum inhibitory concentration (MIC) for infecting organisms. At the same time, for macrolides, it has been reported that high tissue concentrations are achieved, although serum/plasma concentrations remained below the MIC [20][21][22], and this has also been found for tildipirosin [23].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, disease studies using animal models have demonstrated a positive correlation efficacy with extravascular or tissue concentrations of the antibiotics mentioned above the minimum inhibitory concentration (MIC) for infecting organisms. At the same time, for macrolides, it has been reported that high tissue concentrations are achieved, although serum/plasma concentrations remained below the MIC [20][21][22], and this has also been found for tildipirosin [23].…”
Section: Discussionmentioning
confidence: 81%
“…In the case of tildipirosine in cattle, it has been shown that concentrations in lungs exceed the MIC 90 of all target pathogens (1-4 µg ⁄mL) for 16 days (H. somni) or at least 28 days (M. haemolytica and P. multocida), demonstrated in clinical field trials for periods of 21 days, although plasma concentration were under those MIC 90 levels since the first moments after drug administration [10]. Tildipirosin and other macrolides (tulathromycin, gamithromycin, azithromycin, and tilmicosin) have shown clinical efficacy, although plasma concentrations are lower than the MIC 90 levels [7,8,21,22,25], but high lung tissue concentrations are reached. Treatment with tildipirosin potentially offers the advantage of less frequent administration over a shorter duration because of its synergism with serum components and intracellular enzymes, increasing antibiotic uptake by phagocytes and efficacy of intracellular bactericidal enzymes, as demonstrated with other azalides [26].…”
Section: Discussionmentioning
confidence: 99%
“…Serum was obtained by centrifuging blood samples at 4,000 rpm for 10 min and immediately stored at -20°C until analysis (within one month of sampling). Tulathromycin concentrations in serum and lung tissue were determined via HPLC-MS/MS method as described previously [15, 16]. The free fraction ( fu ) of tulathromycin in guinea pig serum was determined in triplicate using Amicon Centrifree Micropartition devices (Millipore, Bedford, MA, USA) with a 10000 Nominal Molecular Weight Limit according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical disease and inflammation has been shown to influence the PK of tulathromycin. In pigs with induced respiratory infections, tulathromycin concentrations in tissues and the elimination half-life increased as compared to that observed in healthy controls [10]. Tilmicosin, another macrolide used in veterinary medicine, has been shown to accumulate in significantly higher concentrations in the lungs of rats with respiratory disease than healthy rats, although serum concentrations were not different between the two groups [11].…”
Section: Introductionmentioning
confidence: 99%